Credibility. Capital Controls, and the EMS. (IMF Working Papers; Working Paper, 1989)
A common rationale for EMS membership is that it enhances the credibility of a central bank's commitment to stable monetary growth. In this paper we consider this idea in the light of two features of the system, namely, the existence of exchange rate bands and the prevalence of capital controls. In our model, capital controls themselves affect credibility, reducing it in the absence of exchange-rate bands but enhancing it when there are such bands. We also show that it is difficult to reconcile the non-zero width of the bands with the credibility-based interpretation of the EMS.